2011
DOI: 10.3399/bjgp11x561168
|View full text |Cite
|
Sign up to set email alerts
|

Central or local incident reporting? A comparative study in Dutch GP out-of-hours services

Abstract: BackgroundCentralised incident reporting in a Dutch collaboration of nine out-of-hours services yielded very few incident reports. To improve incident reporting and the awareness of primary caregivers about patient safety issues, a local incident-reporting procedure was implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“… 37 The three remaining studies scored a moderate in-between rating. 22 29 35 Of the five articles with qualitative research, four had no or an unclear qualitative data analysis description (eg, omitting the types of analysis). Three qualitative studies failed to fully describe their qualitative data collection methods (eg, not mentioning an interview guide or the number of consensus rounds conducted in a Delphi study).…”
Section: Resultsmentioning
confidence: 99%
“… 37 The three remaining studies scored a moderate in-between rating. 22 29 35 Of the five articles with qualitative research, four had no or an unclear qualitative data analysis description (eg, omitting the types of analysis). Three qualitative studies failed to fully describe their qualitative data collection methods (eg, not mentioning an interview guide or the number of consensus rounds conducted in a Delphi study).…”
Section: Resultsmentioning
confidence: 99%
“…A Dutch study which evaluated local and central incident reporting systems suggested that a local incident reporting procedure motivates health professionals to report. Unlike local reporting systems, as described in the same study, the central incident reporting system was found to be useful in addressing generic and recurring patient safety concerns [13]. …”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Several patient safety classifications were reviewed and considered for inclusion, 20,[63][64][65][66] including those developed for general practice. 7,65,[67][68][69][70] These classification systems provided considerable guidance for shaping the scope of the system needed; however, we did not judge that they would support detailed coding of patient safety incidents from general practice.…”
Section: Classification System and Reviewer Trainingmentioning
confidence: 99%